Respuesta del cultivo de fréjol (Phaseolus vulgaris L.) a la aplicación de bioestimulantes foliares y un activador fisiológico. - Tayupanda Ati, Grace Elizabeth (2022)
This research was carried out in the Manguila el Triunfo precinct, La Maná canton, Cotopaxi province, with the objective of determining the response of the bean crop (Phaseolus vulgaris L.) to the application of foliar biostimulants and a physiological activator. A completely randomized block design (CSBD) with five treatments and four blocks or replicates was used, and the statistical analysis was carried out with Tukey's test at 5% probability. The treatments were distributed as follows: (T1= 1 l/ha Biostimulant 1 + 1 l/ha Biostimulant 2; T2= 2 l/ha Biostimulant 1 + 1 l/ha Biostimulant 2; T3= 1 l/ha Biostimulant 1 + 1 l/ha Biostimulant 2 + 1 l/ha Activator; T4= 2 l/ha Biostimulant 1 + 1 l/ha Biostimulant 2 + 2 l/ha Activator; T0= Control). The variables were evaluated at 30, 45, 60 days, which were germination percentage (%), plant height (cm), root length (cm), days to flowering, number of pods per plant, 100-grain weight (g), yield kg ha-1, root weight (g), root volume (cc), aerial weight (g), humidity (%) and dry weight (g). The results obtained at 60 days showed that T1 was superior in terms of plant height with 101.67 cm, moisture percentage 5.67 %, days to flowering in 33.75 days, and yield of 500 kg/ha; while T2 was superior in root length with 46.25 cm, root volume with 8.54 cc and dry weight 58.44 g, with respect to T3 it was superior in root weight with 9.65 g, a number of pods with 23.35 pods per plant and aerial weight 186.24 g, as for the weight of 100 grains the T2 and T3 were equal with 31.25 g. As for the benefit/cost ratio with respect to the implementation of this project, it was determined that the project is profitable since for each dollar invested a profit of $4.51 is recovered.